Advanced Treatment of Tofu Wastewater using Multilevel Filtration and TiO2 Photocatalysis as Promising Approach for Effective Wastewater Remediation - Endi Adriansyah; Marhadi Marhadi; Peppy Herawati; Hariestya Viareco; Rifqi Sufra; Tuty Emilia Agustina (Universitas Diponegoro, 2023)
Tofu production is known to generate large amounts of wastewater containing a variety of organic compounds, chemicals, and potentially hazardous substances. It is very important to apply proper treatment of harmful substances that impact this wastewater. The aim of this study is to explore advanced techniques for treating tofu wastewater by combining multilevel filtration and TiO2 photocatalysis methods. To evaluate the efficiency of the treatment process, influent and effluent parameters, including pH, total suspended solids (TSS), and chemical oxygen demand (COD), are carefully monitored and measured. The results clearly demonstrate the impressive removal efficiency achieved through the combined use of multilevel filtration and TiO2 photocatalysis in treating tofu wastewater. The treated wastewater showed a promising efficiency in pH (100%), a significant decrease in TSS (40%), and COD (72%). the final measurements of pH met the standards set by government regulations, indicating successful remediation of these specific parameters. Even though TSS and COD haven't met the standard limits, each of them shows a very promising efficiency improvement. Towards the end of this study, it is suggested that the combination of these methods holds promise for effectively remediating tofu wastewater.